(untitled) (Revista de Estudos Orientais, 2016)
By approaching a story of one of the leading Israel’s writers, Yehudit Hendel, this paper intends to point out how chronicle-genre’s elements are used to encompass aspects of the narrator /writer’s personal life, transforming the narration into a story where apparently discording elements mingle together.